2017
DOI: 10.1111/efp.12327
|View full text |Cite
|
Sign up to set email alerts
|

Chemical control of two Phytophthora species infecting the canopy of Monterey pine (Pinus radiata)

Abstract: Twelve active ingredients were screened for their ability to control foliage disease caused by Phytophthora kernoviae and Phytophthora pluvialis. Inhibition of mycelial growth and sporangial production of both pathogens were assessed in in vitro assays after exposure to three concentrations of each active ingredient. While most of these active ingredients inhibited mycelial growth in vitro, due to their widespread use, phosphite, copper oxychloride and metalaxyl-M were selected for further study. Four rates of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 37 publications
1
22
0
Order By: Relevance
“…15 years old. Based on the results reported here, copper fungicides, shown to be effective against Phytophthora pluvialis and P. kernoviae in laboratory assays (Rolando et al, 2017, 2019), may be most effective if applied between March and May (Autumn). Copper persists on pine needles for ca.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…15 years old. Based on the results reported here, copper fungicides, shown to be effective against Phytophthora pluvialis and P. kernoviae in laboratory assays (Rolando et al, 2017, 2019), may be most effective if applied between March and May (Autumn). Copper persists on pine needles for ca.…”
Section: Discussionmentioning
confidence: 66%
“…Copper persists on pine needles for ca. 3 months (Rolando et al, 2017), and a spray towards the end of April should protect foliage until at least July, limiting the opportunity for disease to develop. Though further field‐based research is needed before precise operational spray recommendations can be made.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…actinidiae (Cameron and Sarojini, 2014; Gould et al, 2015). Similarly, copper fungicides are widely used by the New Zealand forestry industry for control of dothistroma needle blight (Bulman et al, 2013) and they have recently been shown to be effective against Phytophthora pluvialis (Rolando et al, 2016). However, concerns around soil accumulation and toxicity limit the use of copper sprays in natural environments (Wightwick et al, 2008; Komarek et al, 2010; Kiaune and Singhasemanon, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Exacerbating the effects of Phytophthora infection is the fact that these species are notoriously difficult to control. While Phytophthora share many traits with the true fungi, they are phylogenetically distinct enough to lack many of the canonical molecular targets of labeled fungicides ( Rolando et al, 2016 ). For example, Phytophthora species lack the biosynthetic pathways for ergosterol and a chitin-based cell wall.…”
Section: Introductionmentioning
confidence: 99%